Legends: Autobiographical Sketches - Strindberg, August, 1849-1912 (Salt Lake City, UT : Project Gutenberg, 2014)
"Legends: Autobiographical Sketches" by August Strindberg is a collection of autobiographical essays written in the early 20th century. This work delves into Strindberg's personal experiences, thoughts, and reflections, particularly focusing on the turbulence of his life during his middle years. Through a lens that intertwines existential thought with vivid anecdotal accounts, the sketches explore themes of personal suffering, social critique, and the exploration of the human psyche. At the start of the collection, Strindberg introduces the setting of his life's struggles, particularly emphasizing a period of financial ruin and social isolation while residing in Lund, Sweden. He presents himself as a "possessed exorcist," grappling not only with external adversities, such as lack of financial means and acceptance from society, but also with intense spiritual and psychological turmoil. The narrative paints a picture of a man at war with himself, navigating through loneliness, financial hardship, and the challenge of reconciling his past beliefs with his current reality. With encounters that blur the lines between reality and the supernatural, Strindberg lays the groundwork for a deeply reflective exploration of the human condition, hence setting the tone for the rest of the sketches that follow. (This is an automatically generated summary.)
Release date is 2014-07-24
Produced by Marc D'Hooghe (Images generously made available by the Hathi Trust)
Keywords: Strindberg, August, 1849-1912; Dramatists, Swedish -- 19th century -- Biography